After the rapture : an end times guide to survival - Jeremiah, David, Jeremiah, David 1941- (Nashville, Tennessee : W Publishing Group, 2022)
"What if you or someone you loved missed out on the Rapture? What happens to those who are left behind? Trusted and beloved Bible teacher Dr. David Jeremiah shares the help and hope people will need as they face unfolding events during the End Times"--
Keywords: End of the world; Rapture (Christian eschatology)